Perancangan Sistem Laporan Keuangan Dan Perpajakan Sederhana Berbasis Microsoft Excel Guna Meningkatkan Akurasi Perhitungan Laba Pada UMKM Griya Perabot - putri (Journal of Applied Accounting And Business, 2026)
Griya Perabot MSMEs still face challenges in managing financial and tax records due to manual and poorly organized transaction recording, resulting in inaccurate calculations of operating profit and Final Income Tax obligations. This study aims to design a simple financial and taxation reporting system based on Microsoft Excel to improve the accuracy of profit calculation at Griya Perabot MSMEs. This research employs a qualitative method with a case study approach through observation, interviews, and documentation. The system is developed in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) and adjusted to the capabilities of business owners, covering transaction recording, preparation of simple financial statements, Notes to Financial Statements, and automated calculation of Final Income Tax at a rate of 0.5% of turnover. System testing was conducted through transaction simulations for the November 2025 period. The results indicate that the proposed system improves the organization of financial records, enhances the accuracy of profit calculation, and supports MSMEs in monitoring and preparing for future tax obligations.